Flow Diversion for ICA Aneurysms with Compressive Neuro-Ophthalmologic Symptoms: Predictors of Morbidity, Mortality, and Incomplete Aneurysm Occlusion - Kaiser, D.P.O.; Boulouis, G.; Soize, S.; Maus, V.; Fischer, S.; Lobsien, D.; Klisch, J.; Styczen, H.; Deuschl, C.; Abdullayev, N.; Kabbasch, C.; Jamous, A.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Flow diversion is an effective treatment for aneurysms of the ICA with compression-related neuro-ophthalmologic symptoms, especially when treatment is initiated early after symptom onset and aneurysm occlusion is complete. However, non-negligible complication rates have been reported. Our aim was to identify risk factors for morbidity/mortality and incomplete aneurysm occlusion.MATERIALS AND METHODS: We performed a secondary analysis of a previous publication, which included all patients treated with flow diversion for an unruptured aneurysm of the ICA with compression-related symptoms.RESULTS: Fifty-four patients with 54 aneurysms (48 women, 88.9%; mean age, 59.2 [SD, 15.9] years; range, 21–86 years) treated with flow diversion were included. We observed morbidity and mortality rates of 7.4% and 3.7%. Increasing age (OR per decade, 3.2; 95% CI, 1.23–8.49; P = .02) and dual-antiplatelet therapy with ticagrelor (OR, 13.9; 95% CI, 1.16–165.97; P = .04) were significantly associated with morbidity/mortality. After a median follow-up of 13.3 [SD, 10.5] months, the rates of complete aneurysm occlusion, neck remnant, and aneurysm remnant were 74%, 14%, and 12%. Incomplete occlusion at follow-up was less frequently observed in aneurysms treated with additional coil embolization (OR, 0.1; 95% CI, 0.01–0.86; P = .04).CONCLUSIONS: Although a promising treatment for compressive ICA aneurysms, flow diversion carries a relevant risk for complications and incomplete aneurysm occlusion. Our results may help identify patients in which flow diversion may not be the ideal treatment method. Additional coil embolization increased the likelihood of complete aneurysm occlusion at follow-up.CNcranial nerveFDflow diverterPVOparent vessel occlusion